Brief review on: Fabrication of single electron nano-devices (University of Thi-Qar Journal for Engineering Sciences, 2021)
This paper discusses the fabrication techniques and the fabrication technique of single electron transistor (SET). The SET differs from the conventional CMOS in the sense that it has the ability to control an electron movement so that single electron can be transport at a time, meaning that one by one electron along the channel. This is due to its stunning technique that has the ability of controlling the electron tunneling. The SET represents a promising technology as it offers several unique advantages, example, small size, high operating frequency, and low power consumption. Several SET of fabrication technologies were reviewed in this paper, including quantum dot, carbon nanotube, graphene, and zinc oxide.